2022
DOI: 10.1108/ejm-06-2021-0440
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining age-related loyalty for low-involvement purchasing

Abstract: Purpose Previous research on age-related loyalty is sparse, contradictory and suffers from methodological limitations and criticisms. This study aims to apply two methodological advances to fresh purchasing data to give a much clearer picture of age-related differences in brand loyalty. Design/methodology/approach An online brand choice survey (n = 1,862) is used to examine age-related loyalty within three low-involvement categories in New Zealand. The polarisation index (φ) is adopted as the measure of loya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Next, the study did not find a direct association between age and loyalty. While a null result is not necessarily as interesting as a positive result, this finding still represents another piece of evidence for the body of work on age and loyalty: some other studies have found older buyers tend to be more brand-loyal (East, Harris, Willson, & Hammond, 1995;Lambert-Pandraud et al, 2005) while others find very little difference (Mecredy et al, 2022). It may be that the ageloyalty link exists in some product categories and not others; a question for future research is to identify when, and why, an age-loyalty association is observed or not.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Next, the study did not find a direct association between age and loyalty. While a null result is not necessarily as interesting as a positive result, this finding still represents another piece of evidence for the body of work on age and loyalty: some other studies have found older buyers tend to be more brand-loyal (East, Harris, Willson, & Hammond, 1995;Lambert-Pandraud et al, 2005) while others find very little difference (Mecredy et al, 2022). It may be that the ageloyalty link exists in some product categories and not others; a question for future research is to identify when, and why, an age-loyalty association is observed or not.…”
Section: Discussionmentioning
confidence: 83%
“…However, Yang et al (2005) found mixed results in relation to age and behavioral loyalty, Singh et al found little age‐related differences in brand loyalty in a survey‐based study of Japanese consumers (Singh et al, 2012) and Phua et al (2020) found no clear association between age and behavioral brand loyalty in a study using UK household purchasing panel data. Most recently, Mecredy et al (2022) in a survey‐based study controlled for lower category purchase rates among older buyers by using the Dirichlet‐derived polarization index (Li et al, 2009). The study concluded that older buyers were slightly more loyal in two of the three market contexts studies.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when a brand grows, the brand purchase frequency also slightly increases following the double jeopardy pattern. That is, bigger brands have many more buyers who purchase from them slightly more often (Dawes, 2022; Ehrenberg et al, 1990; Klepek & Kvíčala, 2022; McPhee, 1963; Mecredy et al, 2022). This suggests that the purchase frequency distribution is slightly heavier for growing brands (i.e., everyone purchases slightly more, including the non‐buyers) than for stationary brands.…”
Section: Background and Research Questionsmentioning
confidence: 99%